THE FIRST-YEAR EXPERIENCE INCORPORATING THE ORGANIZATIONAL DEVELOPMENT APPROACH AT KOBE TOKIWA UNIVERSITY - Nakata, Yasuo; Kawasaki, Hiroya; Kozaki, Yasuhiro; Kishida, Aoi; Bannaka, Kenya; Takamatsu, Kunihiko (PEOPLE: International Journal of Social Sciences, 2019)
In Japan, the first-year experience that rapidly gained attention at the beginning of the twenty-first century was clearly positioned in 2008 as formal undergraduate educational programs (The Central Council for Education, 2008). The term “first-year experience” is defined as a “comprehensive educational program primarily created for freshmen” to promote their smooth transition from high school to university and to create successful academic and social experiences at university (The Central Council for Education, 2008). Thus, the first-year experience is a specific program with activities implemented by diverse universities to fit the unique needs of their first-year university students (Tachi, 2008). One important issue of the first-year experience within the undergraduate program has been identifying ways to guarantee the quality of education. Kobe Tokiwa University’s four departments (medical technology, nursing, child education, and dental hygiene) require students to gain strong abilities to collaborate and cooperate in teams to be responsible for future team medical care or a school as a team. Therefore, in 2018, the university implemented a first-year experience program that incorporated the organizational development approach instead of the conventional human resource development approach. This article shares our experiences using a first-year experience program that incorporates the organizational development approach, and we discuss the potential of this approach for the first-year experience. To estimate the effectiveness of organizational development approach in FYE, we analyzed and compared the interim data that were reported on students in 2017 and 2018 using a text mining method. By introducing this “Organizational Development” approach into the students’ first-year educational curriculum, results suggest that it is possible to “deepen self-understanding” and “cooperate in self-understanding of others” at an early stage of a student’s enrollment. It is thought that this approach could become another effective method for universities to use for training professional persons as interpersonal aid workers.